Radiocarbon ages of the sediment core EN21408-2 - Ramesh Glückler; Ulrike Herzschuh (PANGAEA, 2025)
Sediment cores were obtained during fieldwork in August 2021, jointly organized by the Alfred Wegener Institute and the North-Eastern Federal University of Yakutsk. Radiocarbon ages were determined with bulk sediment samples at the MICADAS (Mini Carbon Dating System) laboratory at the Alfred Wegener Institute in Bremerhaven, Germany. More detailed information about the data and an approach to age-depth modelling can be found in the research paper (in preparation). Details of fieldwork in 2021 is available in the corresponding expedition report (Morgenstern et al., 2023).
In: Glückler, R; Herzschuh, U (2025): Radiocarbon ages of eight sediment cores in central and eastern Yakutia, Siberia [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974676